2015
DOI: 10.1007/s00436-014-4292-z
|View full text |Cite
|
Sign up to set email alerts
|

Isoforms of Hsp70-binding human LDL in adult Schistosoma mansoni worms

Abstract: Schistosoma mansoni is one of the most common parasites infecting humans. They are well adapted to the host, and this parasite's longevity is a consequence of effective escape from the host immune system. In the blood circulation, lipoproteins not only help to conceal the worm from attack by host antibodies but also act as a source of lipids for S. mansoni. Previous SEM studies showed that the low-density lipoprotein (LDL) particles present on the surface of adult S. mansoni worms decreased in size when the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Cestode parasites have a reduced capacity for lipid biosynthesis [ 14 ]. In the case of Schistosoma mansoni (trematode), several proteins have been identified as LDL-binding proteins [ 92 , 93 ] and LDL was found associated with parasite’s tegument [ 94 ]. In our study, we found the LDL protein associated with cysts tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Cestode parasites have a reduced capacity for lipid biosynthesis [ 14 ]. In the case of Schistosoma mansoni (trematode), several proteins have been identified as LDL-binding proteins [ 92 , 93 ] and LDL was found associated with parasite’s tegument [ 94 ]. In our study, we found the LDL protein associated with cysts tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HSP is abundant in the excretory/secretory products of the adult Schistosoma japonicum blood fluke [ 31 ]. HSP stimulates diverse immune cells, eliciting release of pro- and anti-inflammatory cytokines [ 32 ], and binds human low-density lipoprotein (the purpose of which is unknown but may be associated with transport of apoprotein B or in lipid trafficking [ 33 ]), and, given these properties, HSP represents a promising vaccine and diagnostic candidate [ 34 ]. Vaults, ribonucleoprotein complexes, are highly conserved in eukaryotes.…”
Section: Resultsmentioning
confidence: 99%
“…Adult worms cannot produce their own cholesterol and must rely on LDL-C from their hosts 51 . Low density lipoprotein binding and internalisation on the schistosomula surface are also mechanisms of alteration 75 . These mechanisms play an important role in this reduction.…”
Section: Discussionmentioning
confidence: 99%